2022
DOI: 10.1093/nar/gkac1194
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions underlying the phase separation of HP1α: role of phosphorylation, ligand and nucleic acid binding

Abstract: Heterochromatin protein 1α (HP1α) is a crucial element of chromatin organization. It has been proposed that HP1α functions through liquid-liquid phase separation (LLPS), which allows it to compact chromatin into transcriptionally repressed heterochromatin regions. In vitro, HP1α can undergo phase separation upon phosphorylation of its N-terminus extension (NTE) and/or through interactions with DNA and chromatin. Here, we combine computational and experimental approaches to elucidate the molecular interactions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(78 citation statements)
references
References 88 publications
4
49
0
Order By: Relevance
“…To understand this behavior and examine the interactions between HP1α and the nucleosome, we quantified the HP1α-DNA interactions by computing the intermolecular contact maps. Figure b shows that HP1α interacts with DNA through patches of positively charged lysine/arginine-rich regions in the hinge, NTE, and CD region, which is consistent with previous experimental and computational studies. ,,, Interestingly, we observed that while the HP1α form contacts with the entire DNA strand, the contact probabilities are generally higher for SHL near the dyad and at the DNA entry and exit sites, contrary to the SHL locations for histone core–DNA contacts (see SI Figure S7a). This suggests that histone tails, which interact favorably with DNA, compete with, and potentially antagonize the contacts between HP1α and DNA, thereby affecting the ability of DNA to promote LLPS of HP1α.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…To understand this behavior and examine the interactions between HP1α and the nucleosome, we quantified the HP1α-DNA interactions by computing the intermolecular contact maps. Figure b shows that HP1α interacts with DNA through patches of positively charged lysine/arginine-rich regions in the hinge, NTE, and CD region, which is consistent with previous experimental and computational studies. ,,, Interestingly, we observed that while the HP1α form contacts with the entire DNA strand, the contact probabilities are generally higher for SHL near the dyad and at the DNA entry and exit sites, contrary to the SHL locations for histone core–DNA contacts (see SI Figure S7a). This suggests that histone tails, which interact favorably with DNA, compete with, and potentially antagonize the contacts between HP1α and DNA, thereby affecting the ability of DNA to promote LLPS of HP1α.…”
Section: Introductionsupporting
confidence: 90%
“…Next, to perform phase coexistence simulation, we resize this cubic box and create an initial slab configuration of dimensions 17 × 17 × 100 nm 3 . After this initialization stage, we run the simulation for 5 μs at T = 320 K and 100 mM salt concentration, as was done in our previous study …”
Section: Introductionmentioning
confidence: 99%
“… 213 HP1α can form condensates, which has a regulatory effect on the growth of breast cancer. 49 , 215 The condensates of RBP non‐POU domain‐containing octamer binding (NONO) regulate tumor cell proliferation by binding to mRNA of proliferation‐related genes. 218 Mutations of speckle‐type pox virus and zinc finger protein alter the formation of condensates and promote breast cancer progression.…”
Section: Biomolecular Condensates Serve As Therapeutic Targets For Di...mentioning
confidence: 99%
“…AKAP95, a nuclear protein that regulates transcription and RNA splicing, supports tumorigenesis by forming condensates and regulating gene expression 213 . HP1α can form condensates, which has a regulatory effect on the growth of breast cancer 49,215 . The condensates of RBP non‐POU domain‐containing octamer binding (NONO) regulate tumor cell proliferation by binding to mRNA of proliferation‐related genes 218 .…”
Section: Biomolecular Condensates Serve As Therapeutic Targets For Di...mentioning
confidence: 99%
“…Using these spectroscopic tools, we dissect the interactions of the CD domain and the CSD dimer with the nucleosome and capture the effect of HP1α phase separation on the nucleosome core and tails. We focus on the interactions between nucleosomes and HP1α phosphorylated at its NTE as this post-translational modification is constitutively present in cells and is a major driving force for phase separation in vitro . ,,, Our results indicate that phosphorylated HP1α primarily contacts the nucleosome through a CD–H3 K9me3 interaction without major rearrangements of the nucleosome core.…”
Section: Introductionmentioning
confidence: 99%